PERENCANAAN LANSKAP PERMUKIMAN BERBASIS MITIGASI BENCANA LONGSOR DI KECAMATAN KINTAMANI KABUPATEN BANGLI - Dewa Ayu Nyoman Ardi Utami; I Made Asna (Jurnal Ilmiah Telsinas, 2019)
Bangli Regency is administratively located in Bali Province. The area of Bangli Regency is divided into 4 Subdistricts and 72 Villages: Susut, Bangli, Tembuku and Kintamani Subdistricts. Kintamani Subdistrict is one of the areas that has a high threat of landslides. Settlements that are still located in high risk landslide areas endanger occupants. Settlement landscape planning based on landslide mitigation needs to be done to prevent losses and casualties due to landslides. This study aims to identify legal aspects, physical, biophysical and social aspects in Kintamani Subdistrict, identify the threat of landslides in Kintamani District, and develop settlement landscape planning based on landslide mitigation in Kintamani District.The research method used refers to a modified planning process ranging from inventory, analysis, synthesis, and planning. The analysis carried out is land suitability analysis for settlement development with reference to the threat of landslide hazard. The mitigation concept is used for settlement planning which is further developed into spatial plans, activities, evacuation, facilities, facilities and infrastructure, circulation and vegetation plans.Settlement landscape planning based on landslide mitigation needs to be done to prevent the occurrence of losses and casualties if landslides also prevent the population from the threat of landslides through appropriate settlement zoning and not in the area of high-scale landslide threat.